Prediction of competition performance via commonly used strength-power tests in junior female weightlifters - Ulupinar, S.; Ince, I. (Isokinetics and Exercise Science, 2021)
BACKGROUND: Strength-power tests are commonly used to monitor performance improvement and to assess preparedness for competition in weightlifters. Previous studies were limited to male weightlifters, consisted of a small number of tests, or used small samples of female weightlifters. OBJECTIVE: The purpose of this study is to determine the strongest indicators of weightlifting performance (WPER) and to reveal the relationships between competition performance and strength-power tests in junior female weightlifters. METHODS: Forty-two female weightlifters (age: 17.8 ± 2.3 years, body mass: 56.6 ± 8.1 kg; height: 156.1 ± 5.8) participated in this study. Participants were tested on a series of performance indicators including Wingate anaerobic power (lower and upper body), isokinetic leg force, vertical jumps, handgrip strength, and isometric leg strength following a national weightlifting competition. Competition performance was calculated with the Sinclair equation. Pearson correlation analysis was used to reveal the relationships between strength-power variables and Sinclair score, and Ridge regression analysis was used to determine the strongest indicators of WPER. RESULTS: The main results showed that Wingate leg peak power (L-PP) and countermovement jump height (CMJ) were the strongest indicators for WPER. They accounted for 74% of the common variance. Additionally, there was a significant correlation between strength-power variables (r= 0.41-0.846) and Sinclair score. CONCLUSIONS: This study`s findings suggest that the strongest predictors of WPER are L-PP and CMJ, and these tests can be used to monitor WPER in junior female weightlifters.